Digital-image Based Numerical Simulation on Failure Process of High-sulfur Coal - Ye Junjian; Zhang Qin; Zuo Yujun; Cheng Wei (Institute of Advanced Engineering and Science, 2013)
Crushing of high-sulfur coal was important for physical desulfurization, but there were little research on crushing mechanism. This paper combined digital image processing technology and rock failure process analysis system RFPA2D to simulate the failure process of high-sulfur coal in Pu'an of Guizhou under uniaxial compression, and discussed the influence of horizontal restraint, existence and different geometric distribution of pyrite particle on mechanical performance and failure process of high-sulfur coal. The numerical results indicated that without horizontal restraint the compressive strength of high-sulfur coal was lower and monomial dissociation of pyrite particle was more sufficient than that with horizontal restraint. The compressive strength of coal containing pyrite particle was larger than that of pure coal and there was stress concentration in upper and lower pyrite particle during failure process. When pyrite particle distributed in the middle position of a coal sample, the compressive strength was higher than that of the other three positions, but monomial dissociation of pyrite particle was more sufficient than that of the other three positions, and this was beneficial to the following desulfurization operation. The study had certain reference value for crushing mechanism, crushing process design, selection of breaking equipment and energy saving and consumption reduction. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1889